Weight gain prevention content delivered to mothers: Lessons from an intervention embedded in a community organization - Tabak, Rachel G.; Morshed, Alexandra B.; Schwarz, Cynthia D.; Haire‐Joshu, Debra (Obesity science & practice, 2019)
Summary Background Transparent reporting of the intervention content study participants receive is particularly important for dissemination and implementation of evidence‐based interventions to address obesity. This study explores intervention delivery and perceptions of content when an intervention is embedded within an organization's usual practice and associations with weight outcomes. Methods This is a secondary analysis from the Healthy Eating and Active Living Taught at Home (HEALTH) randomized trial. HEALTH is a weight gain prevention intervention embedded within a national home visiting programme (Parents as Teachers, PAT). To be consistent with PAT practice, HEALTH has a suggested but also flexible home visit structure. Therefore, the number and frequency of home visits are determined by the family's needs and preferences based on the parent educator's professional judgement. The proportion of participants who received each curriculum core lesson was explored among the 105 families randomized to the HEALTH intervention group, as were mean parent educator perception ratings of the visits (5‐point Likert‐type scale). A chi‐square test was used to examine the association between utilization (ie, low: 1‐6, middle: 7‐12, or high: 13‐18 visits) category and weight maintenance. Results Mothers received on average 13.3 (standard deviation 6.2) core visits. Mean parent educator perception of the mothers' response (out of 5) ranged from 3.99 to 4.27; educators' perception of their own experience with the lesson ranged from 4.13 to 4.34. Among mothers who maintained their weight, 13% were low, 22% were middle, and 65% were high utilizers, while among mothers who gained weight, 3%, 31%, and 67% were low, middle, and high utilizers, respectively; this difference was not statistically significant. Conclusions This study identified wide variation in the visits families received from the curriculum but minimal variation in visit perceptions. Future studies could explore whether there are optimal patterns for visit content, associated with successful outcomes.